Nanofibers Synthesis, Properties and Applications - Kumar, Brajesh (IntechOpen, 2021)
Nanofibers are well known for their vast range of applications in sensors, catalysts, conductors, tissue engineering, and so on, owing to their high surface-area-to-volume ratio, high porosity, and the ease of tuning their structures, functionalities, and properties This book is a comprehensive overview of the synthesis, characterization, and application of nanofibers. Written by experts in the field, chapters cover such topics as green synthesis of nanofibers, electrospinning of carbon nanofibers, applications of ceramic nanofibers, transparent electrodes for flexible and stretchable electronics, nanoribbons, and much more.